2011
DOI: 10.1016/j.prevetmed.2010.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Identification of risk factors associated with highly pathogenic avian influenza H5N1 virus infection in poultry farms, in Nigeria during the epidemic of 2006–2007

Abstract: a b s t r a c tWe conducted a matched case-control study to evaluate risk factors for infection with highly pathogenic avian influenza (HPAI) H5N1 virus in poultry farms during the epidemic of 2006-2007 in Nigeria. Epidemiologic data were collected through the use of a questionnaire from 32 case farms and 83 control farms. The frequency of investigated exposure factors was compared between case and control farms by using conditional logistic regression analysis. In the multivariable analysis, the variables for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 19 publications
2
47
1
Order By: Relevance
“…The space-time cluster interaction was measured at both the spatial and temporal scale using http://repository.uwc.ac.za 6 where n i and n j are the numbers of observations within distance h and time interval t for the pair of events, respectively.…”
Section: Bayesian Krigingmentioning
confidence: 99%
“…The space-time cluster interaction was measured at both the spatial and temporal scale using http://repository.uwc.ac.za 6 where n i and n j are the numbers of observations within distance h and time interval t for the pair of events, respectively.…”
Section: Bayesian Krigingmentioning
confidence: 99%
“…Although vaccination against HPAI was advocated by some (Fasina et al, 2007) and strongly supported by international organizations such as the OIE (Roeder et al, 2006), the Nigerian government decided not to implement a vaccination strategy. Overall, HPAI resulted in the death and culling of approximately 1.3 million birds (Fasina et al, 2011),…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a study amongst poultry farms during the 2006-2007 epidemic of HPAIV H5N1 in Nigeria showed that 'problems with rodent pest control' was not a significant contributor to seropositive flocks. In that study, 55% of case farms and 66% of control farms had rodent problems and a major contributory factor for positive flocks was movement of people (Fasina et al 2011).…”
Section: Association Of Rodents With Aiv Outbreaksmentioning
confidence: 87%